Nevi with hypertrichosis: 1-congenital melanocytic nevus, 2-Becker’s nevus, 3-nevus hypertrichosis, 4-congenital smooth muscle hamartoma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
A circumscribed hypertrichosis of nevus type, namely due to a post-zygotic mutation, which arises in the first period of life and persists with time, occurs as an isolated phenomenon in nevus hypertrichosis, whereas it is associated to other proliferating skin components in congenital melanocytic nevus, Becker’s nevus and congenital smooth muscle hamartoma. Congenital melanocytic nevus is also important because, although rarely, it can degenerate into malignant melanoma. Moreover, physicians should remember that a localized nevus hypertrichosis of the mid line can be expression of a dermal sinus.